SEFALGIA PADA PENDERITA OBSTRUCTIVE SLEEP APNEA DI LABORATORIUM TIDUR RS MITRA KEMAYORAN JAKARTA - Andreas Prasadja*, Maula Gaharu** (NEURONA, 2009)
BACKGROUND CEPHALGIA AND SLEEP DISORDERS HAS CLOSE RELATION BOTH HENCE OBSTRUCTIVE SLEEP APNEA OSA AS ONE OF SLEEP DISORDER FREQUENTLY CAUSES CEPHALGIA THAN OTHER SLEEP DISORDERS